ANALISIS TRANSFORMASI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN PENDIDIKAN BERBASIS SOCIETY 5.0 DI LEMBAGA PENDIDIKAN ISLAM - Siregar, Maralottung; Verawati; Juwita (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
The era of Society 5.0 requires educational institutions to transform toward a learning system that integrates technology, creativity, and humanity. This study aims to analyze the forms, strategies, and challenges of school principals’ leadership transformation in implementing Society 5.0-based education in Islamic educational institutions. This research employs a qualitative approach with a case study design conducted in several madrasahs that apply digital innovation and Islamic value-based learning. Data were collected through in-depth interviews, observation, and documentation, then analyzed using Miles and Huberman’s interactive analysis model. The findings reveal that leadership transformation consists of three main dimensions: (1) visionary leadership that integrates technology with Islamic spiritual values; (2) strengthening teachers’ and students’ digital competence through continuous professional development; and (3) developing an organizational culture based on collaboration and innovation. The challenges encountered include limited digital resources, resistance to change, and technological competence gaps among educators. The study concludes that the success of implementing Society 5.0-based education in Islamic institutions largely depends on the principal’s capacity to balance digitalization and spirituality. The findings imply that leadership development in Islamic education must emphasize both technological literacy and moral-spiritual awareness to create adaptive and human-centered learning environments.